Multimodality 3D image fusion with live fluoroscopy reduces radiation dose during catheterization of congenital heart defects - Buytaert, Dimitri; Vandekerckhove, Kristof; Panzer, Joseph; Campens, Laurence; Bacher, Klaus; De Wolf, Daniël (Frontiers in Cardiovascular Medicine, 2024)
Introduction Imaging fusion technology is promising as it is radiation and contrast sparing. Herein, we compare conventional biplane angiography to multimodality image fusion with live fluoroscopy using two-dimensional (2D)–three-dimensional (3D) registration (MMIF2D−3D) and assess MMIF2D−3D impact on radiation exposure and contrast volume during cardiac catheterization of patients with congenital heart disease (CHD). Methods We matched institutional MMIF2D−3D procedures and controls according to patient characteristics (body mass index, age, and gender) and the seven procedure-type subgroups. Then, we matched the number of tests and controls per subgroup using chronological ordering or propensity score matching. Subsequently, we combined the matched subgroups into larger subgroups of similar procedure type, keeping subgroups with at least 10 test and 10 control cases. Air kerma (AK) and dose area product (DAP) were normalized by body weight (BW), product of body weight and fluoroscopy time (BW × FT), or product of body weight and number of frames (BW × FR), and stratified by acquisition plane and irradiation event type (fluoroscopy or acquisition). Three senior interventionists evaluated the relevance of MMIF2D−3D (5-point Likert scale). Results The Overall group consisted of 54 MMIF2D−3D cases. The combined and matched subgroups were pulmonary artery stenting (StentPUL), aorta angioplasty (PlastyAO), pulmonary artery angioplasty (PlastyPUL), or a combination of the latter two (Plasty). The FT of the lateral plane reduced significantly by 69.6% for the Overall MMIF2D−3D population. AKBW and DAPBW decreased, respectively, by 43.9% and 39.3% (Overall group), 49.3% and 54.9% (PlastyAO), and 36.7% and 44.4% for the Plasty subgroup. All the aforementioned reductions were statistically significant except for DAPBW in the Overall and Plasty (sub)groups. The decrease of AKBW and DAPBW in the StentPUL and PlastyPUL subgroups was not statistically significant. The decrease in the median values of the weight-normalized contrast volume (CMCBW) in all five subgroups was not significant. Cardiologists considered MMIF2D−3D very useful with a median score of 4. Conclusion In our institution, MMIF2D−3D overall enabled significant AKBW reduction during the catheterization of CHD patients and was mainly driven by reduced FT in the lateral plane. We observed significant AKBW reduction in the Plasty and PlastyAO subgroups and DAPBW reduction in the PlastyAO subgroup. However, the decrease in CMCBW was not significant.